Komunikasi Berbasis Empati dan Mindfulness Dalam Pengasuhan - Asis, Asmiaty; Alfiya Syahli Indiyanto; Dewi Multasam; Nurul Khaimah (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2025)
This research focuses on the importance of empathy-based and mindfulness communication in effective parenting to build a harmonious relationship between parents and children. The purpose of this study is to explore how these approaches contribute to children's emotional development and reduce parental stress. The results indicate that the application of active listening techniques, the use of positive language, and emotion management in communication between parents and children promote increased self-confidence, emotional regulation, empathy, and social skills in children. Simultaneously, parents benefit from a better understanding of their children, reduced stress, and strengthened emotional bonds. However, challenges in the modern era, such as distractions and social pressures, often hinder deep communication. Therefore, caregivers are encouraged to develop mindfulness and empathetic communication skills through training or participation in parenting communities. This study affirms that empathy-based and mindfulness communication is crucial as a means to prevent negative impacts on children’s socio-emotional development. Keywords : empathy communication; mindfulness parenting; children’s emotional development